Equivalence and Difference of Semantic Relations in Black Panther Movie Script - Sulvia Fia; Fina Amalia Masri (Program Studi Sastra Inggris Fakultas Ilmu Budaya Universitas Halu Oleo, 2021)
This study used the Black Panther movie script by Ryan Coogler and Joe Robert Cole as the object of the study. The aim of this study is to find out the equivalences and differences of semantic relations used in the Black Panther movie script. This study used Norman Fairclough’s theory that was equivalence and difference of semantic relations. The method used in this study was descriptive qualitative study methods. The primary data was taken from the Black Panther movie script, and secondary data was taken from the audiovisual movie related to the material objects. Techniques of the data collection were downloading Black Panther movie scripts on the internet, reading all the movie scripts repeatedly and comprehensively, checking the words or utterances spoken in the movie script, identifying the semantic relations between clauses and sentences in the form of addition, elaborating, and contrasting in the movie scripts, and then coding the data. The result of the study showed that there were 55 data found, they were Elaboration consists of 14 data, Addition consists of 9 data, and Contrast consists of 32 data. Equivalences of semantic relations were used with the repetition in the form of words, phrases, clauses, and sentences where the purpose has the same perspective or vision. While differences of semantic relations were used by writing a different meaning from the previous clause or sentence.